Repositing Caribbean agriculture : proceedings of the 44th annual meeting (Caribbean Food Crops Society MayaguezPR, 2008)
Presents the plenary session, oral presentations, poster session and T-STAR Invasive Species Symposium.
Keywords: FOOD CROPS